2019
DOI: 10.21608/asnj.2019.56792
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Practices of myocardial Infarction, Patients After Primary Percutaneous Coronary Intervention at Outpatient Clinic in Heart Hospital Assiut University

Abstract: Primary percutaneous coronary intervention (PPCI) is an emergent percutaneous catheter intervention in the setting of ST elevation myocardial infarction, it is the preferred reperfusion strategy. Aim of the study: Assessment of knowledge and practices of myocardial infarction patients after (PPCI). Study design: A descriptive cross-sectional study research design has been utilized. Setting: the study was conducted at outpatient clinic Cardiovascular, Heart Hospital Assiut University. Subjects: A convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
2
0
1
Order By: Relevance
“…The majority of the sample were males (67%), This result was comparable to the results of Mohammad et al (2013) study, which showed that the incidence of myocardial infarction most prevalent among all cases was male sex, where the proportion of males reached (65.9%). Also, this result was agree with a Kamal et al (2019) study that showed that the percentage of males who had suffered a myocardial infarction in Assiut University Heart Hospital was much greater than that of women, where the percentage of male patients was 77%. This was explained by Kamal et al (2019) as men are affected at an earlier age than women and have higher incidence of high blood pressure and led to develop atherosclerosis earlier in life.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of the sample were males (67%), This result was comparable to the results of Mohammad et al (2013) study, which showed that the incidence of myocardial infarction most prevalent among all cases was male sex, where the proportion of males reached (65.9%). Also, this result was agree with a Kamal et al (2019) study that showed that the percentage of males who had suffered a myocardial infarction in Assiut University Heart Hospital was much greater than that of women, where the percentage of male patients was 77%. This was explained by Kamal et al (2019) as men are affected at an earlier age than women and have higher incidence of high blood pressure and led to develop atherosclerosis earlier in life.…”
Section: Discussionsupporting
confidence: 92%
“…Also, this result was agree with a Kamal et al (2019) study that showed that the percentage of males who had suffered a myocardial infarction in Assiut University Heart Hospital was much greater than that of women, where the percentage of male patients was 77%. This was explained by Kamal et al (2019) as men are affected at an earlier age than women and have higher incidence of high blood pressure and led to develop atherosclerosis earlier in life. Also, Abbasi et al (2018) mentioned that gender is a risk factor of cardiovascular disease, where males are at higher risk of MI than women, and males are more likely to suffer MI early at life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation